2018
DOI: 10.1002/jia2.25209
|View full text |Cite
|
Sign up to set email alerts
|

Attrition of HIV‐exposed infants from early infant diagnosis services in low‐ and middle‐income countries: a systematic review and meta‐analysis

Abstract: IntroductionIdentification and retention of HIV‐exposed infants in early infant diagnosis (EID) services helps to ensure optimal health outcomes. This systematic review and meta‐analysis examines the magnitude of attrition from EID services in low‐ and middle‐income countries (LMICs).MethodsWe performed a comprehensive database search through April 2016. We included original studies reporting retention/attrition data for HIV‐exposed infants in LMICs. Outcomes included loss to follow‐up (LTFU), death and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…The interview results revealed that waiting time for the consultations, lack of understanding of how to follow-up, compounded by stigma and fear of disclosure to partners, contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These finding tend to corroborate results from other studies and trials in low resources contexts (10)(11)(12)(13)(14) . HIV testing and ART initiation coverage for mothers tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 91%
“…The interview results revealed that waiting time for the consultations, lack of understanding of how to follow-up, compounded by stigma and fear of disclosure to partners, contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These finding tend to corroborate results from other studies and trials in low resources contexts (10)(11)(12)(13)(14) . HIV testing and ART initiation coverage for mothers tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 91%
“…The interview results revealed that waiting time for clinic visits, and lack of understanding of how to followup added to stigma and fear of disclosure to partners, and contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These findings tend to corroborate results from other studies and trials in low resources contexts [10][11][12][13][14]. HIV testing and maternal ART initiation coverage tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 84%
“…The EID care and treatment cascade has proven challenging in many developing countries, including Mozambique [1,[9][10][11][12][13][14]. Loss-to-follow-up (LTFU) can occur at multiple steps and effective EID is further impeded by human resource constraints, lack of parental understanding for how to navigate care, laboratory stock-outs, and difficulty with patient tracking [9][10][11][12][13][14]. One recent meta-analysis indicated that most attrition occurs in the first 6 months of follow-up and 39% of exposed infants were not in care after 18 months, therefore interventions early in the EID cascade might have greater impact on LTFU [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there will be no treatment available prior to the age of 3 in the near future as this is not requested by the European Medicines Agency (EMA). Therefore, treatment of children with vertically acquired HCV may be complicated as loss to follow‐up in healthcare later in life is likely to be high, as is the case in some settings for HIV …”
Section: Introductionmentioning
confidence: 99%